PENGARUH BAGI HASIL, RELIGIUSITAS, RESIKO DAN PRODUK PADA MINAT NASABAH BANK MUAMALAT - jurnal khitabah; Kikin Mutakin (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2024)
The problems discussed in this research are 1) What is the influence of profit sharing on customer interest in choosing Muamalat Bank in Ciamis Regency. 2) How does religiosity influence customer interest in choosing Muamalat Bank in Ciamis Regency. 3) How does risk influence customer interest in choosing Muamalat Bank in Ciamis Regency? 4) How does the product influence customer interest in choosing Muamalat Bank in Ciamis Regency? The research method used in this research is survey research. Quantitative research methods are a type of research whose specifications are systematic, planned and clearly structured from the start until the creation of the research design. The research results show that Bank Muamalat Indonesia in Ciamis shows very good performance in various aspects, including profit sharing, religiosity, risk and products. However, several areas need to be improved, such as clarity of production sharing agreements, ensuring documents are prepared in simple and easy to understand language, and strengthening team collaborations.